Leadership assessment intrument adaptation, validity and reliability analysis, and an application - Yaşargil, Hande (My University, 2002)
Bu tez çalışması Prof. Warren Bennis’in Linkage Incompany Şirketi için geliştirdiği “Liderlik Değerlendirme Ölçeği”nin bir uygulama ile Türkiye’ye ve Türkçe’ye adaptasyonunun ve ölçeğin geçerlik ve güvenirlilik analizlerini kapsamaktadır. Üç bölümde hazırlanan tezin birinci bölümünde liderlik kavramıyla ilgili genel ve temel teorilerden kısaca bahsedilip teze konu olan “liderlik” değerlendirme ölçeği”ni geliştiren University of Southern California ve Harvard Üniversitesi Porfesörü Warren Bennis’in liderlik yaklaşiımınma odaklanılmıştır. Hemen arkasından ölçeğin detayına bakılarak fonksiyonu, yöneticinin iş hayatında nasıl kullanılabileceği ve ölçek boyutlarında yer alan Liderlik yetkinlikleri ve Liderlik Becerilerinin tanımlanması yer almaktadır. İkinci bölümde ölçeğin türkçeye çevirilerek 98 kişilik yönetici grubuna uygulanması yer almaktadır. Genel Müdür, Genel Müdür’e bağlı birinci ve ikince kademede çalışan yöneticiler olarak tanımlanan örneklem gruptan hem ölçeğin 75 sorusunun cevapları hem de belli sosyo demografik bilgileri toplanmıştır. Üçünce bölümde ise örneklem grubun sosyo demografik analizleri, ölçeğin madde analizleri, geçerlik ve güvenirlilik analizleri yer almaktadır. Bu çalışma Prof.Warren Bennis’in bilgisi dahilinde yapılmıştır.

This dissertation is an adaptation into Turkish of the “Leadership Assessment Instrument” developed for Linkage, Inc., by Prof. Warren Bennis. It also contains a validity and reliability analysis of this assessment. In the first of three parts, I begin with a discussion of the basic tems and concepts of leadership theory in general. I then focus on the specific approaches to leadership developed by Prof. Wrren Bennis. For over 20 years, Bennis has shaped discussions on leadership theory as a prolific writer, faculty member at Harvard University and M.I.T., and the President of the United States. He founded the Leadership Instutute at the University of Southern California, where his scholarship and teaching continues. In order to explain Bennis’ approach, I discuss his definitions of certain leadership competencies and skills which serve as the basis for interpreting his assessment. The first section concludes with a description of how Bennis’ leadership assessment applies specifically to the role of the corporate exectutive. In the second part of the dissertation, I move from theory to applicaiton. Benis’ leadership assessment intrument was translated into Turkish and completed by a population of 98 executivesİ For the purpose of the study, “executives” were defined as those within the first two organizational teirs reporting to a General Manager. In addition to the 75 items on the instrument, I also collected basic socio-demographic information from the population. In the third part, I present an alaysis of the instrument’s validiyt and reliabilty based on my test population. This included s discussion of patterns in the socio-demographic characteristics of the Turkish executives Prof. Bennis has been informed about his dissertation.
Keywords: İnsan Kaynakları Yönetimi; Liderlik; Yetkinlik_Liderlik; Yöneticiler